LAW OF ATTRACTION DALAM PANDANGAN HINDU - Sarma, Nyoman; Agustin, Agustin (Fakultas Dharma Duta dan Brahma Widya, 2025)
Abstrack The concept of Law of Attraction (LoA) has been a topic of great interest, especially in the context of spirituality and self-development. LoA argues that positive thoughts and intentions can attract desired experiences and outcomes into one's life. In this paper, it is explained that a deeper understanding of LoA can be found in Hinduism, which emphasizes the importance of intention and action through the concepts of karma, dharma and reincarnation. Hinduism asserts that every action has consequences, reflecting the basic principle of LoA which suggests that what we radiate out into the universe will return to us. Through literature analysis, this research explores the role of karma phala in the LoA mechanism and the harmony between Bhuana Agung (macrocosm) and Bhuana Alit (microcosm) in its application. It uses Cartesian theory to understand the relationship between mind and body, and emphasizes the importance of mind control in achieving desired outcomes. Emphasis is also given to the philosophy of Tri Hita Karana, which underscores the importance of harmony between man, God and nature. The results show that thinking positively and acting in accordance with good values can maximize the potential for manifestation in life. However, LoA does not only rely on belief, but also requires effort and real action to realize dreams. In conclusion, the application of LoA in daily life should be based on the principles of kindness and mind control, which can lead individuals to a more sustainable and meaningful life.